(untitled) (Journal of Rangpur Medical College, 2026)
Background: Presbycusis is the most prevalent sensory deficit in older adults, its metabolic subtype involves progressive strial microvascular degeneration. Proteinuria, a systemic marker of endothelial dysfunction, may reflect parallel cochlear microvascular damage. Objective: To investigate the association between proteinuria and cochlear dysfunction in elderly patients with presbycusis. Methods: In this cross-sectional study, 340 adults aged ≥60 years with clinically confirmed presbycusis were enrolled and classified by proteinuria status (urine albumin-creatinine ratio [ACR] ≥30 mg/g). The Hearing Handicap Inventory for the Elderly–Screening Version (HHIE-S) and the Absolute Bone Conduction (ABC) test were used to assess functional hearing deficit. Results: Of 340 participants, 112 (32.9%) had proteinuria. The proteinuria group showed significantly higher mean HHIE-S scores (20.4±8.6 vs. 8.2±6.4; p<0.001) and a greater prevalence of markedly reduced ABC results (42.9% vs. 14.0%; p<0.001). A moderately strong positive correlation was found between ACR and HHIE-S scores (r=0.58, p<0.001). Conclusion: Proteinuria is strongly associated with cochlear dysfunction and functional hearing handicap in presbycusis, supporting a shared renal–cochlear microvascular pathology. J Rang Med Col.2026 Mar;11(1): 130-135